Mixed heavy metal stress on photosynthesis, transpiration rate, and chlorophyll content in poplar hybrids - Chandra, Romika; Kang, Hoduck (Forest science and technology, 2016)
The present work aimed to study the physiological effects of mixed heavy metals, cadmium (Cd), copper (Cu), chromium (Cr), and zinc (Zn) in four poplar hybrids. Poplar hybrids were treated once with six different concentrations (0, 5, 50, 100, 200, and 500 ppm) of mixed heavy metals for a period of 3 months. The photosynthetic and transpiration rates were measured before and during treatment using an LCi-SD portable photosynthesis system whereas the photosynthetic pigments were analytically determined. According to the results obtained, poplar hybrids exhibited a decrease in chlorophyll content and carotenoids except for hybrid 1 (Eco 28) which showed an increase at 200 and 500 ppm heavy metal concentrations. The photosynthetic rate decreased with increasing heavy metal concentrations; however, an increase was observed at the highest concentration of 500 ppm at 14.54 µmol m −2 s −1 . Transpiration rates were significantly affected by increased heavy metals. Hybrid 1 (Eco 28) was deduced as the hybrid that has the ability to tolerate high levels of mixed heavy metals. Among the four poplar hybrids tested, hybrid 1 (Eco 28) was the best candidate for phytoremediative experiments under greenhouse conditions. These results are valuable in understanding how various tree hybrids respond to mixed heavy metal stress, especially when using them as bio indicators for phytoremediation experiments.